Feature-Scale Simulations of Particulate Slurry Flows in Chemical Mechanical Polishing by Smoothed Particle Hydrodynamics (Communications in Computational Physics, 2014)
In this paper, the mechanisms of material removal in chemical mechanicalpolishing (CMP) processes are investigated in detail by the smoothed particle hydrodynamics (SPH) method. The feature-scale behaviours of slurry flow, rough pad, waferdefects, moving solid boundaries, slurry-abrasive interactions, and abrasive collisionsare modelled and simulated. Compared with previous work on CMP simulations, oursimulations incorporate more realistic physical aspects of the CMP process, especiallythe effect of abrasive concentration in the slurry flows. The preliminary results onslurry flow in CMP provide microscopic insights on the experimental data of the relation between the removal rate and abrasive concentration and demonstrate that SPHis a suitable method for the research of CMP processes.